Less Alimony after Divorce: Spouses' Behavioral Response to the 2008 Alimony Reform in Germany - Julia Bredtmann; Christina Vonnahme (Institute of Labor Economics (IZA), 2017)
The 2008 alimony reform in Germany considerably reduced post-marital and caregiver alimony. We analyze how individuals adapted to these changed rulings in terms of labor supply, the intra-household allocation of leisure, and marital stability. We use the German Socio-Economic Panel (SOEP) and conduct a difference-in-difference analysis to investigate couples' behavioral responses to the reform. The results do not confirm theoretical expectations from labor supply and household bargaining models. In particular, we do not find evidence that women increase their labor supply as a result of the negative expected income effect. Neither do our results reveal that leisure is shifted from women to men as a response to the changed bargaining positions. In contrast, we find evidence that the reform has led to an increase in the probability to separate for married as opposed to non-married cohabiting couples.
Keywords: J12; J13; J22; 330; alimony; marital instability; female labor supply; intra-household bargaining